Enhancing humanistic care competence in nursing interns: a life education board game pedagogy - Li, Qiong; Yang, Ying; Long, Yun-Ling; Yao, Hua-Qin; Chen, Zhuo-yuanyuan (Frontiers in Education, 2025)
ObjectiveTo study the impact of life education board game teaching on the humanistic care ability and sense of life meaning of nursing interns.MethodsA self-controlled study design was employed. The nursing education management team at the hospital collaboratively developed a life education board game, which is grounded in the Iceberg Theory, Social Learning Theory, Maslow's Hierarchy of Needs, and Positive Psychology as its theoretical frameworks, integrating four teaching objectives into the game. The study involved 90 nursing interns from a tertiary hospital in China. The life education board game teaching activity was implemented in the first department where the interns were assigned. Assessments were conducted using the Care Ability Scale and the Life Meaning Scale at three time points: before the activity, immediately after the activity, and 5 weeks post-activity.ResultsFollowing the teaching activity, nursing interns demonstrated significantly higher scores in the patience dimension (t = 3.102, P = 0.003) and the total care ability score (t = 3.174, P = 0.002) compared to pre-activity scores. At the 5-week follow-up, significant improvements were still observed in the cognition dimension (t = 4.072, P = 0.000), the patience dimension (t = 3.546, P = 0.001), and the total care ability score (t = 4.159, P = 0.000) compared to baseline. However, no significant differences were found in the cognition and courage dimensions of care ability immediately before and after the activity. The courage dimension also remained statistically unchanged 5 weeks post-activity. Regarding life meaning, except for the freedom of will dimension, no significant differences were observed in the scores of other dimensions or the total life meaning score either immediately after the activity or at the 5-week follow-up.ConclusionThis study demonstrates the feasibility of board games in improving humanistic care competence, though long-term impacts on life meaning require further exploration. Future research may consider extending the observation period to more comprehensively assess the impact of life education board game teaching on the sense of life meaning.